LncRNA RNA Component of Mitochondrial RNA-Processing Endoribonuclease Promotes AKT-Dependent Breast Cancer Growth and Migration by Trapping MicroRNA-206 - Huang, Yingdan; Xie, Bangxiang; Cao, Mingming; Lu, Hua; Wu, Xiaohua; Hao, Qian; Zhou, Xiang (Frontiers in Cell and Developmental Biology, 2021)
RMRP was recently shown to play a role in cancer development. However, the function and mechanism of RMRP during cancer progression remain incompletely understood. Here, we report that RMRP is amplified and highly expressed in various malignant cancers, and the high level of RMRP is significantly associated with their poor prognosis, including breast cancer. Consistent with this, ectopic RMRP promotes proliferation and migration of TP53-mutated breast cancer cells, whereas depletion of RMRP leads to inhibition of their proliferation and migration. RNA-seq analysis reveals AKT as a downstream target of RMRP. Interestingly, RMRP indirectly elevates AKT expression by preventing AKT mRNA from miR-206-mediated targeting via a competitive sequestering mechanism. Remarkably, RMRP endorses breast cancer progression in an AKT-dependent fashion, as knockdown of AKT completely abolishes RMRP-induced cancer cell growth and migration. Altogether, our results unveil a novel role of the RMRP-miR-206-AKT axis in breast cancer development, providing a potential new target for developing an anti-breast cancer therapy.